Anatomy of the neurovascular bundle and methods of its preservation with nerve-sparing prostatectomy - H. S. Gevorgyan; A. A. Kostin; N. V. Vorobyev; K. М. Nyushko; A. G. Muradyan; I. A. Taraki; Y. V. Samsonov (Исследования и практика в медицине, 2018)
Providing a high quality of life for a man after performing radical prostatectomy for prostate cancer is currently one of the topical problems of urology and andrology. Nervous-protective radical prostatectomy is one of the high-tech operations in urology and the surgeon’s task is not only to remove the tumor of the prostate gland, but also to ensure a high quality of life for the patient. The importance and urgency of this problem is evidenced by the fact that most of the issues that arise in patients in conversation with a surgeon before surgical intervention are devoted to it.The National Institute of Health of the USA shows that the incidence of prostate cancer is about 9.5% per year, and the localized form began to occur in younger men. In this regard, the surgeon faces the task not only to cure the patient of malignant education, but also to maintain the erectile function and the continent’s indicators, thereby improving the quality of life.At the present stage, diagnostic methods make it possible to detect early prostate cancer much more often, so that the identification and treatment of such patients become more accessible and allows the use of this operation. However, for the preservation of the neurovascular bundle, it is mandatory to know the anatomical features of this zone.Over the past few decades, anatomical studies have been conducted that described the neuroanatomy of the prostate and the adjacent tissue. This article summarizes the latest results of studies of neuroanatomical studies, some of which contradict the established consensus on pelvic anatomy.